Heutagogi dalam Pendidikan: Strategi Meningkatkan Kemandirian Belajar Peserta Didik Sekolah Dasar - Aep Saepudin; Dudung Abdu Salam (Jurnal Lensa Pendas, 2025)
heutagogy approach is a learning strategy that gives students freedom in determining their own learning methods, resources, and strategies. This approach focuses on developing learning independence, critical thinking, and problem-solving skills, which are key in facing educational challenges in the digital era. This study uses a literature review approach by analyzing various academic sources and online articles that discuss the implementation of heutagogy in elementary school learning. Data were collected from relevant research journals and scientific reports to understand the effectiveness and challenges in the application of heutagogi. The analysis shows that heutagogy can increase learners' intrinsic motivation, strengthen lifelong learning, and help them develop adaptive skills in the face of change. However, the implementation of this approach faces challenges such as students' readiness to learn independently, the skills of educators in guiding heutagogi-based learning, and limited access to educational technology. In order for heutagogy to be implemented effectively, there needs to be a combination strategy, such as blended learning, as well as training for educators and the provision of adequate infrastructure. With the right strategy, heutagogy can be an innovative solution to create elementary school students who are more independent, creative, and ready to face global challenges.